PENINGKATAN KEMAMPUAN LITERASI DIGITAL DI LINGKUNGAN PENDIDIKAN BERBASIS APLIKASI CANVA - Juliawan Wayan; Roro Dwi Umi Badriah; Ni Wayan Suastini; I Wayan Susanta; I Nyoman Rajeg Mulyawan; Sri Datuti (Sewagati, 2025)
The purpose of this community service activity is to enable teachers at SMK N 1 Sukawati, Gianyar Regency, to utilize the Canva application and create learning media based on Canva for various materials used during classroom learning. The mechanism of the community service method in implementing the activity generally consists of planning/preparation, implementation, assistance, and evaluation. The study was conducted with 6 teacher respondents at SMK N 1 Sukawati. From this community service activity, it can be concluded that the implementation of the Canva application training to improve digital literacy ran well. The teachers were able to create learning media and other products using the Canva application. This is evident from the evaluation results, which showed a significant increase in teachers’ knowledge and skills, as well as their enthusiasm in creating Canva-based learning media.